An investigation of a novel monolithic nickel-based catalyst for clean hydrogen production - Shen, Ziqi (Cranfield University, 2024)
The decarbonisation of the energy sector can anticipate the future of net zero, and hydrogen is currently one of the most promising energy carriers to contribute to this goal. As for hydrogen production, steam methane reforming (SMR) occupies the predominant status and will remain in its position in the short term. The SMR process requires high-performance catalysts such as nickel-based catalysts, and carbon capture technology is of interest to decarbonise the SMR to produce clean hydrogen. The overall aim of the PhD project is to develop a novel monolithic nickel-based catalyst and evaluate its performance under SMR and sorbent-enhanced SMR (SE-SMR) conditions. The literature review looked back on the ceramic materials used in the SMR and SE-SMR processes, and also the method to prepare nickel-based catalysts. Silicon carbide was chosen as the support material due to its excellent thermal and mechanical properties. The monolithic nickel-based catalysts were designed, synthesised, characterised and tested in a fixed-bed reactor, in which the main reactor pipe and the steam generator were designed and constructed for this project. In addition, a pulse injection system was designed and installed on the reactor, and the SMR kinetics were studied using the monolithic catalysts. After the integration of the solid sorbents, a further study was conducted on the effect of structure within the SE-SMR process using the monolithic catalysts. The monolithic catalysts exhibited excellent activity at low SMR temperatures and pressures with a realistic gas space velocity. A kinetic model was established to describe the reaction rates using a novel and time-saving approach. The mass transfer limitations led to a low activation energy in kinetics and a reduction in activity when sorbents were applied. The monolithic catalysts will be a strong candidate for the decarbonisation of the energy sectors, with further improvement of its long-term stability and coordination with appropriate sorbents.
Nabavi, Seyed A. - Associate Supervisor Wagland, Stuart T. - Associate Supervisor
Keywords: Structured catalysts; steam methane reforming; intrinsic kinetics; monolith; reaction mechanism; carbon capture